Effect of Newtonian heating/cooling on free convection in an annular permeable region in the presence of heat source/sink. Issue 1 (11th August 2020) - Anurag; Singh, A. K.; Chandran, P.; Sacheti, N. C.
Abstract: The influence of Newtonian heating/cooling in the presence of heat source/sink has been investigated on laminar free convective flow in a vertical annular permeable region. The mathematical model for the problem has been considered as a boundary value problem consisting of two simultaneous ordinary differential equations. The boundary value problem has been transformed to nondimensional form. This has given rise to a number of parameters representing both geometrical and physical features of the problem. Closed‐form analytical solutions of the governing equations have been obtained for two different cases of internal heat generation/absorption. To assess the effects of governing parameters on the fluid velocity and temperature, a number of profiles of these field variables have been presented. The efficacy of the distinct processes on the field variables has been discussed extensively. The main outcome obtained in this study is that the velocity as well as temperature is enhanced in the case of the Newtonian heating while the opposite behavior occurs in the Newtonian cooling for both cases of source and sink. Furthermore, the influence of the governing parameters has been shown on the skin friction, volume flow rate, and the Nusselt number.